(3UHGHI GdeYGfi hUHGHI GdeYGfis - (3CHh HcQ eMjj GdOjf Hf Jbj GdOjf GdSdWj GdOeTbj,J (B1107 (3g` s
(3ChdgG (B:s
(3jbhd GdYHO GdabjQ Edi ehdGg GdeYWi , hMi GdOjf GdOeTbi GdSdWi dWa Gddg Hg (B: (3GdMeO def Cdge GdUH ai MjQJg QTOg s
(3BNQgG (B:s
(3heP UM YfOi Cf CbUi eQGOce cJGH ZRjQ GdaVd djS jYGH LYdJ dce gPG GdcJGH gOjI hNjQ LdjS ai GdReGf cJGH JeJ GdQSGdI GdehSheI HUHGI GdeYGfi hUHGHg GdeYGfi s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B60 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B240s
Keywords: (3GdJUha hGdBOGH GdTQYjIs